Voices and values in the news: News media talk, news values and attribution. (March 2016) - Bednarek, Monika
Abstract: This paper explores how discourse analysis can be used to investigate the construction of newsworthiness in news media talk via the establishment of nine news values: Timeliness, Consonance, Negativity, Impact, Proximity, Unexpectedness, Superlativeness, Personalisation and Eliteness. It compares linguistic approaches to news values and discusses cognitive, social, material and discursive aspects of news values. Focusing on broadcast news, the paper illustrates how discursive news values analysis can be combined with analysis of attribution strategies. Analyses show how voices are integrated and how news values are combined and packaged. The paper argues that bringing together news values analysis and attribution analysis can provide detailed insights into journalistic practice. Highlights: Compares linguistic approaches to news values. Discusses cognitive, social, material and discursive aspects of news values. Explores discursive news values analysis. Combines news values analysis with analysis of attribution strategies. Focuses on broadcast news.